The spatial dimensions of collective memory: disagreements regarding ‘Plaza de la Patria’ in Puan (province of Buenos Aires) (Huellas, 2015)
In the last decades there was a boom of studies and debates dedicated to the question of memory. In this context, the "geography of memory" (Foote y Azaryahu, 2007) contributed to analyze the spatial dimensions and explore the relationships between collective memory, places and national identities. The objective of this paper is to explore the role of historical monuments with a nationalistic sense in the town ofPuan(Buenos Aires), in the constitution of local identities, in this case linked to the origins of the town under the advance over the "desert".For this, the conflict around the maintenance of the “Plaza dela Patria”, a public space dedicated to the commemoration of the “Desert Campaign” where the monument of the Unknown Soldier is located, will be analyzed. The dispute began in 2012 when the Municipal Government and a group of investors announced the construction of a hotel in the proximity of this historical monument. Immediately, a group of neighbors, the so called "Group Plaza dela Patriaas it is" began to demonstrate against the hotel's future location, arguing that the place is important to preserve the "heroic" past of the town.
Keywords: memory; “geography of memory”; historical monuments; nationalism; identity